PEMANFAATAN MEDIA KOMUNIKASI DINAS KEBUDAYAAN DAN PARIWISATA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN MANCANEGARA DI KOTA BATAM - Agistini, Silvia; Abidin, Sholihul (SCIENTIA JOURNAL, 2021)
Batam City is the largest city in the Riau Archipelago and also one of the most visited cities both domestic and foreign tourists. This is because Batam City is geographically located in international hub lanes which are directly off to Singapore’s south coast and Malaysia. The purpose of this research is to find out the benefits of the website pages as an information platform of communication that can be used by the Department of Culture and Tourism to increase the number of foreign visitors to the Batam City. This research also aims to find out about how the communication pattern of the Department of Culture and Tourism manage to increase the number of foreign visitors in Batam City. The method used in this research is a qualitative research method. Technically collecting data in this research means by interviews and observations. Based on the results of the research, it can be concluded that the utilization of the website carried out by the Department of Culture and Tourism in Batam City Office is quite able to help to increase the number of foreign tourist visiting the City of Batam by several factors that affect the effectiveness of information shared through social media website. As well as for the communication pattern used by the Department of Culture and Tourism in Batam City Office, named the downward communication pattern.